Workplace bullying and its preventive measures and productivity among emergency department nurses - Suhair Hussni Al-Ghabeesh; Haya Qattom (BMC, 2019)
Abstract Background Workplace bullying has adverse effects on nurses' productivity and emotional well-being and increases nurses' desire to leave their jobs. Bullying is a common phenomenon that has been reported worldwide. Emergency Department (ED) nurses are particularly exposed to bullying as a result of their job stressors and demands. Purposes To examine the prevalence of bullying and the impact of preventive measures on productivity among Jordanian ED nurses; and to examine bullying in relation to personal and organizational factors. Methods We surveyed ED nurses in five hospitals in Amman, Jordan - two government hospitals and three private hospitals. The eligibility criteria for the study, met by 134 persons, were having at least an associate degree and having worked in the ED for at least six months. We used a four-part questionnaire that included demographic data, the Negative Acts Questionnaire, questions on prevention of bullying, and a health and productivity survey. Data analysis included descriptive and inferential statistics. Results A total of 120 ED nurses joined the study, an 89.6% response rate. The majority of participants were male (65%) and their mean age was 29.4 years. Ninety percent of the participants reported being bullied. Nurses with less experience in the ED were exposed to more bullying compared to other nurses. Of nurses who reported being bullied, 61.7% reported associated decreased productivity, including the ability to respond to cognitive demands, provide support, appropriate communication, safe care, and competent care. The overall mean score for the prevention of bullying questionnaire was 94.51 out of 168 (SD = 23.43). Drilling down, the highest mean score was for the "Individual sub-scale", and the highest item mean score was for "I know the process of how to report bullying". Conclusion Bullying is prevalent among ED nurses in Jordan; it has significantly influenced the nurses' perception of their productivity and the quality of care they provide. Although nurses reported adopting measures to prevent bullying, they were insufficient to address this widespread problem. Implications for nursing and health policy Bullying is a common occurrence in nursing practice in Jordan, as in other places. It has a detrimental effect on the quality of health care. Accordingly, interventions, which we describe, should be undertaken to minimize the incidence and impact of bullying.